2013
DOI: 10.1007/s10649-013-9517-z
|View full text |Cite
|
Sign up to set email alerts
|

A boundary-crossing approach to support students’ integration of statistical and work-related knowledge

Abstract: Vocational students and beginning professionals typically find it hard to integrate the mathematics and statistics that they have learned at school with work-related knowledge.To explore how such an integration process could be supported, we conducted an intervention in secondary vocational laboratory education. Our boundary-crossing approach was informed by the literature on boundary crossing and accompanying learning mechanisms (e.g., reflection in the form of perspective making and taking, and transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 26 publications
0
39
0
5
Order By: Relevance
“…In our view, this highlights the need for a holistic view on concepts and techniques, and shows that integration of different types of knowledge is required to draw sensible conclusions (cf. Bakker and Akkerman 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our view, this highlights the need for a holistic view on concepts and techniques, and shows that integration of different types of knowledge is required to draw sensible conclusions (cf. Bakker and Akkerman 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Such a focus does not necessarily give much insight into the fine-grained inferential structure of practices or how actions, knowledge, and emotion can be interwoven. Yet such fine-grained analysis may be useful for designing learning environments, not only in vocational education where actions and practical knowledge are evidently important (Bakker and Akkerman 2014), but also in general education that aims to take coordination (coherence and integration) seriously and seeks for holistic development of students' knowledge, skills, and attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But, learning at the boundaries does not happen easily and needs explicit support (Akkerman & Bakker, 2011;Ludvigsen et al, 2010;Wenger, 2000). Whether explicit support stimulates students' boundary crossing activities and learning is a question that has not yet been studied in the context of higher education (Akkerman & Van Eijck, 2013;Bakker & Akkerman, 2014). In earlier studies, the theoretical concept of boundary crossing is found to provide a good lens for understanding learning that occurs when people learn across practices (e.g.…”
Section: 2mentioning
confidence: 99%